Ultrasound-Guided Percutaneous Neuromodulation in Patients with Unilateral Anterior Knee Pain: A Randomized Clinical Trial - Paula García-Bermejo; Blanca De-la-Cruz-Torres; Carlos Romero-Morales (Applied Sciences, 2020)
The objective of this study was to evaluate the short-term and crossover effects of a percutaneous neuromodulation (PNM) intervention on the femoral nerve, regarding the pain, knee flexion motion (range of motion (ROM)), and functionality, in patients with unilateral anterior knee pain (AKP). Our study used a randomized clinical trial design. Thirty patients were divided into two groups: one asymptomatic knee group in which patients received stimulation in the femoral nerve corresponding to the nonsymptomatic knee; and one symptomatic knee group, in which patients received stimulation in the femoral nerve corresponding to the painful knee. Pain, knee flexion ROM, Victorian Institute of Sport Assessment-Patella (VISA-P) and Kujala questionnaires were evaluated. Twenty-eight patients completed the study. Compared to their baseline values, both groups showed an increase immediately at 24 h, and at 1 week for the knee flexion ROM variable. In addition, the symptomatic knee group showed an increase for the Kujala score and a decrease for the numeric rating scale (NRS) variable from baseline to 1 week. VISA-P score did not show statistically significant differences for the time-group interaction. After the intervention, there were no differences between the groups in any measured time. Conclusion: a single-shot ultrasound-guided PNM intervention per week in the femoral nerve may be an effective treatment for improving the pain, knee flexion ROM, and knee functionality. In addition, this technique produces crossover benefits in the nonintervention limb.